The politics of memoir and the Northern Ireland conflict - Hopkins, Stephen 1967- (Liverpool University Press, 2013)
This book examines memoir-writing by many of the key political actors in the Northern Irish ‘Troubles’ (1969–1998), and argues that memoir has been a neglected dimension of the study of the legacies of the violent conflict. It investigates these sources in the context of ongoing disputes over how to interpret Northern Ireland’s recent past. A careful reading of these memoirs can provide insights into the lived experience and retrospective judgments of some of the main protagonists of the conflict. The period of relative peace rests upon an uneasy calm in Northern Ireland. Many people continue to inhabit contested ideological territories, and in their strategies for shaping the narrative ‘telling’ of the conflict, key individuals within the Protestant Unionist and Catholic Irish Nationalist communities can appear locked into exclusive and self-justifying discourses. In such circumstances, while some memoirists have been genuinely self-critical, many others have utilised a post-conflict language of societal reconciliation in order to mask a strategy that actually seeks to score rhetorical victories and to discomfort traditional enemies. Memoir-writing is only one dimension of the current ad hoc approach to ‘dealing with the past’ in Northern Ireland, but in the absence of any consensus regarding an overarching ‘truth and reconciliation’ process, this is likely to be the pattern for the foreseeable future. This study provides the first comprehensive analysis of a major resource for understanding the conflict
Title from publisher's bibliographic system (viewed on 11 Aug 2017)
Keywords: Rhetoric / Political aspects / Northern Ireland; Autobiographical memory / Political aspects / Northern Ireland; Political violence / Northern Ireland / History / 20th century; Social conflict / Northern Ireland / History / 20th century; Nordirlandkonflikt; Autobiografie; Northern Ireland / History / 1968-1998